Students’ Responses Toward Kahoot Application in Indonesian Subject - Lilis Amaliah Rosdiana (Universitas Suryakanca, 2019)
This article aims to describe university students' responses toward Kahoot! application in Indonesian subject. Kahoot! application is commonly played by gamers in their smartphone. However, the writer used this application as a medium of teaching Bahasa Indonesia, more specifically during the quiz. The quiz was conducted once in the session of the subtopic Ejaan Yang Disempurnakan (EYD). The research method used in this study was descriptive method, with questionnaire as the research instrument. The results show that the students were more motivated, more enthusiastic and able to manage their time to think throughout the quiz. There was no tense atmosphere, and all students seemed happy and enthusiastic in answering each question. The Students and the lecturer were able to utilize their smartphones for something they never imagined before, that was, to learn by utilizing Kahoot! application.Keywords: students' responses, Kahoot! application, Indonesian subject